Handgrip strength measurement protocols in individuals with Down syndrome: a systematic review and meta-regression<subtitle>Handgrip strength measurement protocols and Down syndrome</subtitle> - Geiziane L. R. Melo; Rafaela C. Espírito Santo; Viney P. Dubey; Cesar Agostinis-Sobrinho (Annals of Medicine)
Background Handgrip strength (HGS) serves as a robust predictor of overall strength across various populations, including individuals with Down Syndrome (DS).Objective To analyze the HGS measurement protocols used in studies involving individuals with DS.Methods Primary sources were sourced from six databases: PubMed, Scopus, Ovid, Embase, ERIC, and Web of Science, spanning from inception to 23rd December 2023. Inclusion criteria focused on individuals with DS, compared with control groups, and examined HGS measurement protocols and outcomes. Meta-regression was utilized to assess bias associated with HGS values concerning different measurement protocols.Results Out of 29 studies involving 1816 participants, most controlled for body position (65%), arm position (82%), elbow position (82%), wrist position (62%), handgrip duration (55%), hand adjustment to dynamometer (62%), verbal encouragement (75%), and familiarization (44.8%). The number of reported variables in the HGS protocol was significantly associated with an increase in HGS, with a mean estimate of 20.59 units (SE = 2.59, p < 0.0001, 95% CI [15.49–25.68]), though there was notable heterogeneity (I2 = 94.33%). The spline regression analysis showed that the model explained 82.66% of the variation in HGS, with adults having 47.61 units higher HGS than children (p = 0.0009), while obesity was linked to a decrease of 15.68 units (p = 0.0675). Sample size and group had no significant effects.Conclusion Overall, protocols for assessing HGS in DS studies are comprehensive yet heterogeneous. Higher HGS values correlated with adherence to standard protocols.